HEMATOLOGICAL PROFILES OF AFRICAN CATFISH (Clarias gariepinus) THAT ARE MAINTAINED BY BIOFLOC SYSTEMS - Kurniawan, Ahmad Juli; Syawal, Henni; Lukistyowati, Iesje (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTThe researcher conducted this research from November to December 2018 in two places: Ambon Farm Pekanbaru and the Laboratory of Parasites and Fish Diseases, Faculty of Fisheries and Marine Sciences, Riau University. This research aims to obtain information about hematological profiles of African catfish that are maintained by biofloc systems. The research method used in this study is the survey method. From the sampling location, ware collected as much as 30 African catfish (15 male and 15 female), with a length of 20-25 cm.Sampling was done three times with a span of 14 days. Every sampling ware collected as much as 10 African catfish (5 male and 5 female). Blood sampling is done directly at location and hematological parameter measured at Laboratory. Total erythrocyte and leukocyte measured were Klonz (1994), hemoglobin levels (Wademeyer and Yasutake, 1977), haematocrit and leucocrit levels (Anderson and Siwicki, 1995). The results shows that the hematological value of male African catfishs, total erythrocytes 197.7 x104 cells/mm3, hematocrit 24.4%, hemoglobin 7.3 g/dL, total leukocyte 236.6 x103 cells/mm3, leukocrit 2.86%, while the total erythrocyte of female African catfish is 195.6 x104 cells/mm3, hematocrit 23.7%, hemoglobin 6.7 g/dL, leukocyte total 222.2 x103 cells/mm3, leukocrit 2.26%. Water quality parameters of bioflok ponds during as research were in the ranges, temperature 25-260C, pH 6.7-71, dissolved oxygen 2.8-3.1 mg/L, dan ammonia 0.958-1.235 mg/L.Key Words : Hematological, Clarias gariepinus, Biofloc